Evaluasi Pengguna Hospital Management Information System (HMIS) dengan Metode End User Computing Satisfaction (EUCS) di Instalasi Rawat Jalan RSUP Dr. Kariadi Semarang - Sabran Sabran; Muhammad Yunus; Arniati Ramadhani (Sekawan Institut, 2023)
The Hospital Management Information System (HMIS) is basically used in various service pro-cesses starting from patient registration to the payment process which is expected to streamline the performance of the hospital and provide credible information for its users. As technology develops, HMIS has been used in various hospitals, one of which is to support all aspects of in-creasing customer satisfaction. RSUP Dr. Kariadi Semarang has Type A accreditation status which is a teaching and referral hospital in Central Java. Seeing the high activity at RSUP Dr. Kariadi, customer satisfaction is one of the references. Therefore this study focuses on evaluating consumer satisfaction using the End User Computing Satisfaction (EUCS) evaluation model through direct interviews. The four variables used include Content, Accuracy, Format, Ease of Use, and Timelines. Based on the results of the analysis, there are 3 dimensional factors that have fulfilled user satisfaction, namely the dimensions of content, accuracy, and format. Even though it is stated that it meets user satisfaction, these dimensions still need to be improved because they still have weaknesses in terms of multiple patient data collection and identification of new patients and old patients. The other two dimensions, namely the dimensions of timeliness and ease of use, are still not sufficient for user satisfaction because of the capabilities of the devices used and the lack of guidance in the system.